Exchanging experiences of technology partnership: The Helsinki meeting of experts (New York, 1996)
The bookpresents the papers prepared for an expert group meeting organized by the Finnish Ministry of Trade and Industry and UNCTAD's Division for Science and Technology, in cooperation with the Programme for Development Cooperation at the helsinki School of Economics (PRODEC), and held in Helsinki in April 1996. Its purpose was to exchange experiences on technology partnership for capacity-building and competiveness.
Keywords: development countries